A Reaction to "Modernist Poetic Practices in English Poetry from Southeast Asia: A Comparison Between Jose Garcia Villa and Arthur Yap" - Chua, Jonathan (Archīum Ateneo, 2024)
This follow-through develops Patke’s characterization of Jose Garcia Villa as a heroic figure by an account of the reception to his poetry in the Philippines since World War II. Villa’s insistence on the primacy of art alienated him from critics in the late sixties and seventies who saw him as a “mental colony.” Later postcolonial criticism, however, allowed for a more favorable interpretation of Villa.